Beyond knockout rats: New insights into finer genome manipulation in rats - Huang, Guanyi (Landes Bioscience, 2011)
The ability to “knockout” specific genes in mice via embryonic stem (ES) cell-based gene-targeting technology has significantly enriched our understanding of gene function in normal and disease phenotypes. Improvements on this original strategy have been developed to enable the manipulation of genomes in a more sophisticated fashion with unprecedented precision. The rat is the model of choice in many areas of scientific investigation despite the lack of rat genetic toolboxes. Most recent advances of zinc finger nucleases (ZFNs) and rat ES cells are diminishing the gap between rat and mouse with respect to reverse genetic approaches. Importantly, the establishment of rat ES cell-based gene targeting technology, in combination with the unique advantages of using rats, provides new, exciting opportunities to create animal models that mimic human diseases more faithfully. We hereby report our recent results concerning finer genetic modifications in the rat, and propose their potential applications in addressing biological questions.